New sustainable Mannich-functionalized lignin flocculants for ultra-efficiently tailoring wastewater purification. (10th February 2023) - Wang, Bin; Cao, Xue-Fei; Yu, Shi-Xin; Sun, Zhuo-Hua; Shen, Xiao-Jun; Wen, Jia-Long; Yuan, Tong-Qi
Abstract: The complex pollutants in wastewater, especially the highly toxic and carcinogenic azo-dyes, seriously endanger the water ecosystem and human health. Using renewable lignin to develop efficient flocculants is of great significance to environmental sustainability. Nevertheless, the preparation process of lignin-based flocculant is not only inefficient and cumbersome, but also brings serious pollution, making their development unsustainable. In this study, a new type of ultra-efficient Mannich-functionalized lignin-based flocculants was prepared by a simple, green strategy. Lignin-based flocculants were synthesized by copolymerizing lignin with acrylamide in a UV-induced aqueous copolymerization system and then modified by Mannich with formaldehyde and diethylenetriamine. Comprehensive considering the influence of molecular weight, charge density and amphiphilicity, herein, two different types of lignin-based flocculant (LBF1 and LBF2) could be precisely tuned by adjusting the dose of formaldehyde and diethylenetriamine. The results showed that the turbidity removal rate of LBF1 for kaolin suspension could be up to 99.31%, and the decolorization rate of Acid Black 1, Direct Red 80 and Reactive Red 2 solutions using LBF2 was more than 99.60%, which outperformed almost all other lignin-based flocculants reported in the previous reports. Moreover, LBF1 and LBF2 showed excellent resistance to the complex external environment, reflecting their outstanding universality. Graphical abstract: Image 1 Highlights: The Mannich active sites of acrylamide-grafted lignin were greatly increased. New sustainable Mannich-functionalized lignin-based flocculants were prepared. The water-soluble flocculant had a 99.31% removal rate for kaolin suspension. The flocculant with a high charge density showed excellent decolorization effects. The flocculation mechanisms of lignin-based flocculants were investigated.